The importance of affectively-laden beliefs about health risks: the case of tobacco use and sun protection - Janssen, Eva (2012)
Affect is gaining prominence in health behavior research. However, little is known about the relative influence on behavior of specific affectively-laden beliefs about health risks (affective likelihood, worry, anticipated regret), particularly in comparison to cognitive likelihood beliefs. We investigated this issue in relation to two very different cancer-related behaviors. In two prospective studies [tobacco use (N = 1,088); sunscreen use (N = 491)], hierarchical linear and logistic regression analyses revealed that affectively-laden risk beliefs predicted intentions and behaviors more strongly than cognitive likelihood beliefs. Cognitive likelihood contributed independently only for sunscreen use intentions. Smoking-related outcomes were most strongly associated with anticipated regret. Sunscreen-related outcomes were most strongly associated with affective likelihood. Affectively-laden beliefs might be stronger predictors of some cancer-related behaviors than traditional cognitive likelihood measures. Including affective aspects of health risk beliefs in health behavior interventions and theoretical models, including investigating their interrelationships in different behavioral contexts, could advance both theory and practice.